Can turbo-roundabouts and restricted crossing U-Turn be effective solutions for urban three-leg intersections? - Fernandes, Paulo (2023)
This research explored the potential of replacing conventional single-lane roundabouts by turbo-roundabouts and yield- and stop-controlled restricted crossing U-Turn (RCUT) at intersections located in urban corridors. A simulation approach based on a well-integrated assessment of traffic performance, emissions and driving volatility indicators of alternative intersection designs (AIDs) is therefore a major contribution of the study. The paper also addressed the impacts that several locations of the U-Turn crossovers have on travel and idling times, as well as on carbon dioxide and nitrogen oxides emissions. Traffic, pedestrian, and cyclist flow data were collected from two urban three-leg single-lane roundabouts. A microscopic simulation platform of traffic and emissions (respectively, VISSIM and vehicle specific power) was used to evaluate intersection-specific design and operations. The results indicated that turbo-roundabout and yield-controlled RCUT outperformed the existing single-lane roundabout at the two sites. Turbo-roundabout generally yielded the lowest travel times and emissions compared to the other intersections. The Yield-RCUT also performed better than the single-lane roundabout for U-Turn crossover located 100–170 m from the main intersection. Our findings bring a solid basis for academic research and transportation planners to promptly consider the implementation of AIDs and contribute to sustainable mobility in cities.